Evaluation of green spaces using fuzzy systems - Mota, M. T. [UNESP]; Roveda, J. A.F. [UNESP]; Roveda, S. R.M.M. [UNESP] (Springer Nature, 2018)
Green urban areas have natural attributes that provide important environmental services. However, their impacts depend on the local characteristics, so it is necessary to evaluate the environmental potentials of such areas individually. The lack of methodologies to assess the quality of green urban areas led to the implementation of the present work, which proposes a calculation model for assessing the environmental quality of these spaces. The construction of the model used fuzzy systems capable of handling the subjectivity of the variables, with the creation of fuzzy rule-based systems that permitted working with parameters of different natures. The variables employed were the percentage of vegetation in the area in question and its quality, the latter being determined by analysis of the degree of maturation. Forest formations were considered potentially more advantageous for the provision of environmental services, compared to savannah and grasslands. The model was constructed considering the physical and biological characteristics of the city of Sorocaba, as well as Brazilian standard classifications of vegetation types and their successional stages.